Conjugational transfer of gentamicin resistance plasmids intra- and interspecifically in Staphylococcus aureus and Staphylococcus epidermidis. - McDonnell, R W (1983)
We have previously reported the transfer of gentamicin resistance (Gmr) plasmids in a mixed culture inter- and intraspecifically between strains of Staphylococcus aureus and Staphylococcus epidermidis isolated at Michael Reese Hospital (Jaffe et al., Antimicrob. Agents Chemother. 21:773-779, 1982). We have now shown that representatives of these plasmids were transferred between apparently nonlysogenic strains of S. aureus either in mixed culture in broth or by filter-mating on agar medium. The mechanism of transfer appeared to be conjugation. A transferable Gmr plasmid (pSH8) mobilized or cotransferred a tetracycline R-plasmid and a chloramphenicol R-plasmid that were not independently transferable. The transfer of Gmr plasmids was accompanied by a high incidence of deletion mutations with varied loss of plasmid resistance determinants and, with some mutants, loss of the ability to effect self-transfer. Restriction endonuclease digestion of pSH8 and its deletion mutants made it possible to assign the property of self-transfer to a specific segment of the pSH8 genome and provided the basis for a physical and genetic map of that plasmid. Similar Gmr plasmids from S. aureus strains isolated in locations remote from Michael Reese Hospital had resistance determinants and transfer properties comparable to those of pSH8. Our observations provide evidence for the conjugal transfer of some staphylococcal plasmids, apparently independent of the presence of phage. This mechanism may be of significance in the intra- and interspecific dissemination of resistance to aminoglycosides and other antibiotics in Staphylococcus spp.